Trends and challenges in Higher Education in Latin America (Adaya Press, 2026)
This book features twenty-four chapters providing a comprehensive analysis of the current challenges and trends in Latin American Higher Education. The volume explores the integration of technological resources—such as MOOCs, digital platforms, and pedagogical assistants—alongside the implementation of active learning methodologies and competency-based education. Through research conducted in institutions across Mexico, Colombia, Brazil, Argentina, and Central America, the authors examine critical issues including academic quality, university governance, interculturality, attention to diversity, and factors influencing student dropout rates. This collection offers a multidisciplinary perspective on how teaching innovation and digital transformation are redefining the educational landscape throughout the region.